METHODS FOR SOLVING CERTAIN LOGICAL PROBLEMS IN PRIMARY EDUCATION - Burkhonova Feruza Bakhtiyor qizi (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract. This article is devoted to the methodological foundations of teaching students to solve logical problems in primary school. Developing mathematical reasoning and logical thinking in pupils during problem-solving processes plays a crucial role in their intellectual growth. The paper discusses the step-by-step formation of the concept of a logical problem, the use of visual methods, and lesson organization considering students’ individual characteristics. It also highlights methods that foster curiosity and independent reasoning in students.